Organizational Niches and the Dynamics of Organizational Founding - Baum, Joel A. C.; Singh, Jitendra V. (Organization Science, 1994)
In this paper we argue that patterns of organizational niche overlap and nonoverlap influence the organizational niches in which entrepreneurs create organizations. Organizational niches characterize the different resource requirements and productive capacities of individual organizations in a population. Depending on which organizational niches are targeted, entrepreneurs will face different competitive landscapes. For a population of day care centers (DCCs), we measure organizational niches and compute organizational niche overlaps in terms of the ages of children they are licensed to enroll. Using weights based on organizational niche overlaps, we disaggregate population density (i.e., the number of DCCs) into overlap density and nonoverlap density to measure the potential for competition and cooperation among DCCs. The overlap density of an organizational niche is equal to population density weighted by the overlaps of the focal organizational niche with all other organizational niches. Conversely, non-overlap density is equal to population density weighted by the absence of overlaps of a focal organizational niche with all other organizational niches. We hypothesize that overlap density will be negatively related to the founding rate. We expect entrepreneurs will be much less likely to target or be capable of founding organizations in crowded parts of the resource space than parts that are less densely populated. We also hypothesize that nonoverlap density will be positively related to the founding rate. This is because differentiated DCCs do not compete directly for resources, and, at the same time, their presence can have facilitative influences through complementary demand enhancement and widening social acceptance of the organization form. Supporting these predictions, a dynamic analysis showed that overlap density had a competitive effect on the founding rate, while nonoverlap density had a positive effect. Parallel effects were obtained when overlap and nonoverlap densities were further disaggregated on the basis of geographic proximity into local and diffuse components. Overall, our findings are consistent with earlier research on organizational founding at the population level, but reveal intrapopulation patterns of mutualism and competition that influence the likelihood of organizations being established in different organizational niches. The key result of this study, that location in a multidimensional resource space, together with the distribution of other competitors and noncompetitors, has a significant impact on founding probabilities serves to illuminate some of the underlying dynamics of competition and mutualism that impact strategic and entrepreneurial processes.